PENINGKATAN JIWA ENTREPRENEUR BAGI PEMUDA DAN PENGELOLA KARANG TARUNA DI KELURAHAN CIJOHO KABUPATEN KUNINGAN - Nur Komarudin, Munir; Suhardi, Dadang; Prayudi, Deri; Masruroh, Rina (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M), 2024)
Abstract Currently, young man is the spearhead of economic improvement in the village or sub-district where they live. Today's youth organizations pay less attention to the entrepreneurial aspect in each of their activities. Therefore, the purpose of this activity is to increase the entrepreneurial spirit for youth or youth managers in Cijoho Village. The methods used are knowledge transfer, discussion and question and answer as well as direct practice with Canva's business model. The results of this study are an increased understanding of the importance of entrepreneurs and understanding of creating a Canva business model. Keywords: entrepreneurship, entrepreneur, bussines model canva